REDESIGN OF DESA WISATA LEREP’S VISUAL IDENTITY AND ITS APPLICATION ON PROMOTIONAL MEDIA AS AN EFFORT TO BUILD DESTINATION BRANDING - Afthoni, Riza (Arty: Jurnal Seni Rupa, 2020)
Lerep Village was declared a tourist village in 2016, which aims to improve the welfare of the village community and introduce traditions and culture in Lerep village. Based on the preliminary study, the problem faced by the tourist village of Lerep is a logo that has the same visualization as several other tourist villages in Central Java. Therefore, the village manager and the research team initiated a redesign of the visual identity used to build destination branding, which was applied to promotional media. The process of redesigning the visual identity and its application in the promotional media for the Tourism Village of Lerep went through several processes, they are (1) The pre-production process (2) The production process, including content design, consultation, and final design. (3) The post-production process, including work cast and presentation of works. This design produces logos, icon sets, sign systems, stationary sets, digital marketing (Instagram, website), flyers, and travel map.